If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17x + -28x + -12 = 21 Reorder the terms: -12 + 17x + -28x = 21 Combine like terms: 17x + -28x = -11x -12 + -11x = 21 Solving -12 + -11x = 21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -11x = 21 + 12 Combine like terms: -12 + 12 = 0 0 + -11x = 21 + 12 -11x = 21 + 12 Combine like terms: 21 + 12 = 33 -11x = 33 Divide each side by '-11'. x = -3 Simplifying x = -3
| Y+13.4=8.63 | | 2r+10=14 | | 3/5a=18 | | 18b-6= | | -1x+9=7x-5 | | x^6-4x^5+13x^4=0 | | z^4+4iz+10i=0 | | -16y+18=-30 | | (1/5)^(x-9)=5^(7x-5) | | -3+8x=-59 | | 75=25t+4.9t^2 | | 0.6(x-4)=12.0 | | 38a+21-20a=39 | | -1x-9=7x+5 | | 75=25*t+0.5*9.8*t^2 | | 9(x+4)+x=3(x+5)-8 | | -5(y-3y)+9=3(2y-y)+1+12y | | .50c+.40-400=190 | | 0.05x-2.75=0.3(x-5) | | 3=-3(x+4) | | -1x+9=7x+5 | | 6x+2-15=-15 | | .50c+.40=400 | | -3(x+4)+4=7(x+4)+3 | | 5(x-7)+10=3(x-5) | | h(t)=2t-t^2 | | 5sinx+7cosx=8 | | 12x-8=9x-8 | | x-4=-24-9x | | .50c+400=.40 | | (2x-5)=15 | | -3(t-5)+7t=6t-5 |